(untitled) (Research, Society and Development, 2020)
The article aims to propose a theoretical-analytical model for the study of work under the logic of managerialism in the light of Psychodynamics of Work (POW). The proposal is based on the recent changes in the logic of production, in the world of work and, consequently, in the social fabric, which indicate a scenario characterized by flexibility, individualism and hyperactivity. POW is suggested because it is a theoretical current capable of examining the object studied from the prism both of the context dimensions (work conditions, work organization and work relationships) as well as content (psychic load, identity construction, etc.), typical of the relationship man-work, which shape the experiences (fear, pleasure-suffering) and can interfere in the state (health-illness) of the subjects. As for the method, the model it presents, as a qualitative proposal, the use of the interview as data collection, of the Analysis of the Core of Sense (ACS) as an interpretive technique. In addition, it presents, in quantitative terms, as a data collection technique, the Inventory on Work and Illness Risks (IWIR), based on the scales that assess the dimensions related to work. The methodology used in making this work was a bibliographic review, with categorization of literature using the thematic analysis technique. As a result, the work gave rise to a methodological framework, which can be used as a methodology in future research.